ANALISIS KESESUAIAN LAHAN TANAMAN PADI SAWAH DI KABUPATEN KONAWE SSELATAN PROVINSI SULAWESI TENGGARA - La Baco; Hasbullah Syaf; Lukman Yunus; Sahindomi Bana (Universitas Halu Oleo, 2020)
Land suitability analysis becomes important as a source of information about the distribution of land that can be developed for Paddy Rice. The objective of the study was to analyze the level and distribution of land suitability of paddy fields in South Konawe District. This research was conducted in the Sub Districts of Laeya, Palangga, Baito and Lalembuu for 3 months namely October-December 2017. The research method used was a survey method and laboratory analysis of soil samples and data analysis of soil and climate characteristics. Data analysis includes determining the type and intensity of limiting factors, suitability classes and technological recommendations for limiting the development of paddy fields. The results showed that the area of prospective locations in Laeya Sub District was 259 hectares, Palangga Sub District covering 312 hectares, Baito Sub District covering 1,021 hectares and Lalembuu Sub District covering 159 hectares. Types of limiting factors the development of paddy field were low cation exhange capacity (CEC) low N and P levels, acidic pH and moderate drainage. The land suitability class for all locations analyzed was S2 with a category suitable enough for the use of Paddy Rice. The limiting factor improvement technology recommendations were the addition of organic matter, liming, N fertilization, P fertilization and drainage channel construction. The adoption of these recommendations will increase the carrying capacity of land for the growth and production of paddy fields.Keywords:cation exchange capacity, land suitability, land quality,, limiting factors, paddy fields